Short‐ and long‐term outcomes of polyethylene band attenuation of congenital extrahepatic portosystemic shunts in dogs: 60 cases (2010‐2020). (11th September 2022) - Glenn, O.; Tomlinson, A.; Pinchbeck, G.; Burrow, R.
Abstract : Objectives: To report the short‐ and long‐term outcomes following attenuation of congenital extrahepatic portosystemic shunts in dogs using a novel polyethylene band. Materials and Methods: Records were retrospectively reviewed for dogs that underwent congenital extrahepatic portosystemic shunt attenuation by a polyethylene banding technique, at a single institution between 2010 and 2020. Short‐term outcome data were collected from peri‐operative clinical records with follow‐up examinations, scheduled at 6 and 18 weeks post‐operatively, and post‐operative imaging when performed. Long‐term follow‐up was collected by validated owner questionnaire, telephone interview or medical records. Long‐term outcomes were categorised by "excellent", "good" or "poor". Results: Sixty dogs were included. Post‐operative complications occurred in 10 of 60 dogs (16.7%), four major and six minor, with a peri‐operative mortality of 6.7%. Persistent shunting was identified in nine of 53 dogs (17%) available for follow‐up examination and four dogs underwent a revision surgery. Long‐term follow‐up was available for 44 dogs at a median of 75 months post‐operatively (range 7 to 128). Long‐term outcomes were "excellent" (26) or "good" (8) in 81.8% of dogs and "poor" (8) in 18.2%. At the time of follow‐up, 30 of 44 (68.2%) dogs were not receiving any medical treatment and 27 of 28 (96.4%) questionnaire respondents were satisfied with the response to surgery. Clinical Significance: Polyethylene band attenuation of congenital extrahepatic portosystemic shunts provides comparable outcomes to cellophane. The material used in this study is widely available and consistent while being pre‐sterilised and pre‐folded makes it easy to use.